Anaesthetic efficacy of incorporating different additives into lidocaine for the inferior alveolar nerve block: A systematic review with meta‐analysis and trial sequential analysis. (22nd April 2022) - Iranmanesh, Pedram; Khazaei, Saber; Nili, Mahsa; Saatchi, Masoud; Aggarwal, Vivek; Kolahi, Jafar; Khademi, Abbasali
Abstract: Background: Incorporating an additive into lidocaine is a method to enhance the efficacy of the inferior alveolar nerve block (IANB) in mandibular posterior teeth. Objectives: To assess the efficacy of incorporating additives into lidocaine in the success rate of IANB for teeth with the diagnosis of normal pulp (NP) or symptomatic irreversible pulpitis (SIP). Methods: Randomized controlled trials (RCTs) assessing the incorporation of additives into lidocaine on the pulpal anaesthesia success rate of mandibular posterior teeth were searched in PubMed, Scopus, Web of Science, Ovid, EBSCO, Embase, and Cochrane databases up to 1 December 2021. The risk of bias (RoB) was assessed by the Cochrane Risk of Bias Tool. A random‐effects model was employed to calculate the pooled risk ratio (RR) with a 95% confidence interval (CI), using STATA 16. The trial sequential analysis (TSA) was applied to calculate the required information size (RIS). The Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach was used to assess the certainty of the evidence. Results: Of 6966 records retrieved initially, 14 trials (8 for NP and 6 for SIP groups) were included in qualitative and quantitative syntheses. All trials were categorized as low and unclear RoB for NP and SIP groups, respectively. In the NP group, with 307 participants, no significant effect was observed for additives incorporated into lidocaine (RR: 0.84; 95% CI: 0.53‒1.32; I 2  = 98%). Subgroup analysis revealed that adding mannitol led to a higher success rate (RR = 1.24; 95% CI: 1.15–1.34; I 2  = 7.16%). In the SIP group, with 434 participants, no significant effect was shown when the additives were incorporated (RR = 1.22; 95% CI: 0.98–1.52; I 2  = 0%). Likewise, in subgroup analysis, incorporating mannitol or sodium bicarbonate demonstrated no significant effect (RR = 1.76; 95% CI: 0.93–3.32; I 2  = 18.41% and RR = 1.06; 95% CI: 0.65–1.72; I 2  = 53.5%, respectively). Discussion: TSA revealed that the outcome was "inconclusive" for each group. The certainty of the evidence was graded as "very low" and "low" for NP and SIP groups, respectively. Conclusions: The very low to low certainty of evidence indicated that incorporating additives into lidocaine did not increase the efficacy of IANB and supplemental injections are still necessary to help practitioners achieve painless dentistry. Registration: PROSPERO database (CRD42020132585).